GAMBARAN TINGKAT PENGETAHUAN TENTANG PERTOLONGAN PERTAMA PADA LUKA BAKAR DALAM PEMANFAATAN EKSTRAK LIDAH BUAYA (ALOE VERA L) DALAM SEDIAAN GEL - Tya Muldiyana; Aldi Budi Riyanta; Rizki Febriyanti; Eli Supriatin; Redo Saputra (LPPM Universitas Bina Bangsa, 2024)
MAN 1 Tegal is a formal education located on Jl. MA' Hadut Tholabah Babakan Lebaksiu Islamic Boarding School so it is commonly known as MAN Babakan Lebaksiu because it is located in Jatimulya Village, Lebaksiu District, Tegal Regency. The purpose of this Community Service (PKM) activity is to try to improve knowledge and skills to students through counseling and training on the use of aloe vera extract (Aloe vera L) in gel preparations as a burn medicine and establishing a cooperative relationship between Politeknik Harapan Bersama Tegal and MAN Babakan Lebaksiu as a partner. The methods used are surveys, interviews, providing material and practicum as well as distributing questionnaires as feedback from partners and evaluating PKM activities. The results of this activity began with an explanation and counseling about burns. In addition, there were question and answer sessions, discussions, filling out questionnaires and practice of making gels. There are several conclusions that can be drawn. The conclusion of this activity shows that the training activity for making gel from aloe vera extract went well and was proven to increase students' knowledge with a sufficient score of 63%.